PENINGKATAN GERAK DASAR MANIPULATIF MEMUKUL BOLA MELALUI MODIFIKASI PERMAINAN ROUNDERS PADA PESERTA DIDIK KELAS V SEKOLAH DASAR - Baihaqi, Aden; Surisman; Putri, Alifia Ramadhina; Priyono, Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low ball-striking skill of Grade V-B students at SD Negeri 1 Pengajaran. It aimed to improve students’ manipulative fundamental movement skill in ball striking through modified rounders games. Classroom Action Research was conducted in two cycles, each comprising planning, action, observation, and reflection. The participants were 20 students (10 boys and 10 girls). In Cycle I, students practised with a bat having an 8-cm striking surface; in Cycle II, the surface was reduced to 6 cm, while all evaluations used the same standard bat. Data were collected through a performance test assessing arm swing, body position, ball contact, and ball direction, and through a student-activity observation sheet. Data were analysed using mean scores, mastery percentages, the Lilliefors normality test, and a paired-samples t-test. The mean score increased from 52.9 in the pre-cycle to 60.4 in Cycle I and 79.6 in Cycle II. Learning mastery increased from 0% to 40% and then to 85%, while student activity rose from 80.00% to 86.67%. Both pre-cycle and Cycle II data were normally distributed. The paired-samples t-test showed a significant improvement (t = 17.169 > t critical = 2.093; df = 19). Therefore, progressively modified rounders games effectively improved elementary students’ ball-striking skill and learning participation.